Surface Instability of Composite Thin Films on Compliant Substrates: Direct Simulation Approach - Nikravesh, Siavash; Ryu, Donghyeon; Shen, Yu-Lin (Frontiers in Materials, 2019)
Surface instability via wrinkle formation is a common feature in thin films attached to a compliant substrate. Wrinkled thin-film structures have been increasingly exploited to enhance device performance. In this study, a numerical technique utilizing embedded imperfections is employed for direct simulations of wrinkle formation, extending from a single-film structure to composite films involving two or more layers. The incorporation of material elements, bearing different elastic properties at the film-substrate interface, assists in triggering buckling instability when the compressive strain reaches a critical value. The wrinkle wavelength and amplitude obtained from the numerical modeling show excellent agreements with available theoretical solutions involving bi-layer composite films, over the entire span of volume ratios of the constituent layers. A valid range of imperfection distribution, resulting in uniform wrinkle formation, is identified. The current numerical approach is robust and easy to implement and yields great promises in generating reliable wrinkling patterns. It can be readily applied to cases where realistic features cannot be captured by theories, such as the generalized plane strain deformation, indirect compression, and multilayer composite films.